GRADUATE QUALITY MANAGEMENT STUDY: EXPLORING GRADUATE TRACER STUDIES IN HIGHER EDUCATION (OPPORTUNITIES AND CHALLENGES) - Johansyah, Rizky; Julaiha, Siti; Muadin, Akhmad (Jurnal Manajemen Pendidikan, 2025)
This approach was pioneered by Schomburg and a team of researchers at the University of Kassel, through the International Centre for Higher Education Research (INCHER-Kassel). Their research involved multiple countries with the aim of collecting empirical data that serve as a basis for evaluating higher education programs. Quality assurance has become a crucial aspect in assessing the improvement of higher education quality. Graduate tracer studies serve as one of the methods to evaluate the relevance and quality of graduates. A literature study approach is used to further examine the implementation of graduate tracer studies in identifying various challenges and opportunities for developing graduate quality management. Data condensation, data presentation, conclusion drawing, and data verification and validation are the stages used in this research. The results indicate that the opportunities presented by graduate tracer studies point to a paradigm shift, the development of responsive curricula, mapping of labor market trends, and enhancement of institutional reputation. However, challenges faced include low participation rates and limitations in data processing and follow-up actions. This study implies that the application of graduate tracer studies plays a vital role as a tool in graduate quality assurance.